Standar Ganda Politik Luar Negeri Amerika Serikat Terhadap Kudeta Mesir 2013 - Wahyudi, Herry (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2018)
This research will examine the double standards of US foreign policy against the coup in Egypt in 2013, given that the US intervention against the Middle East region is very dominant. Attention and the US response be different in response to the case of the coup in Egypt. US seemed to not make this case as a priority despite the coup led to the violation of human rights and democracy. The response shown by the US is very different compared to the US intervention against Iraq and Libya are rated US itself as defending human rights and democracy in the region. The purpose of this research is to find out why the US double standards in its foreign policy related to the Egyptian coup. Data will be explored through literature method (library research). Overall the data will be correlated with foreign political theory of rational actor models that can explain the reason for choosing the attitude of the US double standard in a coup in Egypt in 2013 based on the selection and cost-benefit considerations on the measures taken. The results of this paper indicate that the indication of the double standards shown by the US to Egypt coup influenced by the victory of the Muslim Brotherhood (IM) as a political Islam that could interfere with the stability and US interests in the Middle East. Some of the options and the consequences have been considered by the US in response to the case, including participating ignoring their violations of democracy and human rights in the case even though it was contrary to the foundations and principles of US foreign policy. Another indication that support multiple standards is the response of US allies in the Middle East, such as Israel, Saudi Arabia and the United Arab Emirates who consider IM as a threat to the stability and the Middle East region. Keywords: US double standards, US foreign policy, coup Egypt, political Islam, Muslim Brotherhood Penelitian ini akan mengkaji standar ganda politik luar negeri Amerika Serikat terhadap kudeta di Mesir tahun 2013, mengingat bahwa intervensi AS terhadap kawasan Timur Tengah sangat dominan. Perhatian dan respon AS terlihat berbeda dalam menanggapi kasus kudeta di Mesir. AS seolah tidak membuat kasus ini sebagai prioritas walaupun kudeta tersebut berujung pada pelanggaran HAM dan demokrasi. Respon yang diperlihatkan oleh AS sangat berbeda jika dibandingkan dengan intervensi AS terhadap Irak dan Libya yang dinilai AS sendiri sebagai upaya penegakan HAM dan demokrasi di kawasan tersebut. Tujuan dari penelitian ini ialah untuk mencari tahu mengapa AS bersikap standar ganda dalam politik luar negerinya terkait dengan kudeta Mesir. Data akan ditelaah melalui metode kepustakaan. Keseluruhan data akan dikorelasikan dengan teori politik luar negeri model aktor rasional yang dapat memaparkan alasan AS untuk memilih sikap standar ganda dalam kudeta Mesir 2013 berdasarkan pemilihan dan pertimbangan untung-rugi atas tindakan yang telah diambil. Hasil dari penelitian ini menunjukkan bahwa indikasi standar ganda yang diperlihatkan oleh AS terhadap kudeta Mesir dipengaruhi oleh kemenangan Ikhwanul Muslimin (IM) sebagai political Islam yang dapat mengganggu stabilitas dan kepentingan AS di Timur Tengah. Beberapa pilihan dan konsekuensi telah dipertimbangkan oleh AS dalam merespon kasus ini, termasuk ikut mengabaikan adanya pelanggaran demokrasi dan HAM dalam kasus tersebut walaupun hal tersebut bertentangan dengan landasan dan prinsip politik luar negeri AS. Indikasi lain yang mendukung standar ganda ialah respon sekutu AS di Timur Tengah, seperti: Israel, Arab Saudi, dan Uni Emirat Arab yang menganggap IM sebagai ancaman bagi stabilitas dan kawasan Timur Tengah. Kata kunci: standar ganda AS, politik luar negeri AS, kudeta Mesir, politik Islam, Ikhwanul Muslimin